Nightmare Proneness Predicts Nightmare Frequency Incrementally Over Neuroticism and Distress - Kelly, William E.; Zamora, Richard C.; Park, Soeun (Sleep Science, 2024)
Introduction Previous research found that nightmare proneness, a purported disposition to experience frequent nightmares, accounted for nightmare frequency independent of neuroticism and distress. However, these findings may have been the result of reduced reliability and content validity of the measures. The current study aimed to replicate these findings using established, lengthier measures of neuroticism and distress.Materials and Methods In the present cross-sectional study, 230 university students completed measures of nightmare frequency, nightmare proneness, neuroticism, and distress.Results Regression models found that nightmare proneness incrementally predicted nightmare frequency above neuroticism and distress. Additional analyses indicated that neuroticism and distress indirectly predicted nightmare frequency through nightmare proneness, whereas nightmare proneness was not associated with nightmares through neuroticism or distress.Conclusion Nightmare proneness was statistically separable from neuroticism and distress. The results and suggestions for future research to better understand the nightmare proneness variable are discussed.
Keywords: nightmare Frequency; neuroticism; psychological distress; nightmare proneness